Nonlinear Fault Detection Based on An Improved Kernel Approach - Wang, Guang; Jiao, Jianfang (IEEE access, 2018)
Quality-related issue is a recently raised subject that attracts a lot of attention in process monitoring community. Since most industrial processes present more or less nonlinear characteristics, the study of nonlinear quality-related methods is thus very necessary. Most of the existing methods are based on a kernel partial least square (KPLS) model; however, they usually have a very large amount of computation due to the iterative computation of KPLS. To make matters worse, the logic of these methods is complex, since they use four subspaces to detect a fault. In this paper, we will propose a new kernel-based method whose computation only involves eigenvalue solution and singular value decomposition. Besides, it has a simple logic using only two subspaces. What is more, it has a stable performance with high computational efficiency. All these advantages of the new method are demonstrated by simulation results.